Resveratrol suppresses hyperoxia-induced nucleocytoplasmic shuttling of SIRT1 and ROS production in PBMC from preterm infants in vitro. (3rd May 2018) - Yang, Xi; Dong, Wen-Bin; Lei, Xiao-Ping; Li, Qing-Ping; Zhang, Lian-Yu; Zhang, Ling-Ping
Abstract: Objective: By assessing silent mating-type information regulation 2 homolog 1 (SIRT1) nucleocytoplasmic shuttling and reactive oxygen species (ROS) levels in peripheral blood mononuclear cells ( PBMCs), this study aimed to explore the role of SIRT1 in premature infants after exposure to hyperoxia and assess the protective effects of resveratrol (Res). Methods: Firstly, ROS levels as well as SIRT1 translocation and expression in PBMCs samples were evaluated from 40 premature infants with different oxygen amounts received at birth. Then, PBMCs, from additional 40 premature infants administered no oxygen at birth, were used to establish an in vitro model of hyperoxia. Results: In infants that received O2 at birth, ROS and MDA levels, and SIRT1 translocation rates gradually increased in a concentration-dependent manner, while SIRT1 gradually decreased. In agreement, PBMCs cultured in vitro showed increased ROS levels after exposed to hyperoxia, SIRT1 translocation increased as well. However, treatment with Res resulted in opposite effects. Conclusion: Res inhibits ROS release in PBMCs from preterm infants exposed to hyperoxia, likely by preventing SIRT1 nucleocytoplasmic shuttling and increasing SIRT1 expression.